SIFAT FISIKOKIMIA DAN ORGANOLEPTIK TEPUNG MOCAF (MODIFIED CASSAVA FLOUR) DENGAN FERMENTASI MENGGUNAKAN EKSTRAK KUBIS - Wikanastri Hersoelistyorini; Sri Sinto Dewi; Andri Cahyo Kumoro (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
This research aimed to study the use of cabbage extract as the source of lactic acid bacteria (LAB) onthe swelling power, solubility, amylose content, and organoleptic properties of mocaf. The researchwas carried out through two experimental steps with the first step aimed to study the optimumfermentation time based on swelling power of the mocaf. Whereas second step aimed to determine theoptimum cabbage extract concentration based on swelling power, solubility, amylose content, andorganoleptic properties. The results showed that optimum swelling power was achieved fromfermentation using 40% cabbage extract for 24 hours, optimum solubility was obtained using 60% and80% cabbage extracts, lowest amylose content was achieved by fermentation using 40% cabbageextract. The favored aroma, color and texture were obtained from fermentation using 20%, 40% and80% cabbage extract, respectively. The best fermentation condition was determined based on thelowest amylose content as low amylose means high amylopectin. Amylopectin plays important role intriggering the process of  puffing, by which food products will be light, porous, dry and crunchy.Mocaf with lowest amylose content is recommended as raw material for the manufacturing of cookies. Keywords: cabbage extract, lactic acid bacteria, mocaf, physicochemical properties, swelling power.